Do ut des, czyli rzecz o darze w dyplomacji. Przypadek siodła z daru sułtana Mustafy II dla posła Stanisława Małachowskiego z 1699 roku - Lorenc, Magdalena (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2014)
The paper attempts to answer the question of the reasons and consequences of applying the ceremonial custom of exchanging gifts in Polish-Turkish diplomatic relations in the 17th century. The ‘gift’ was understood as an object presented, that was typically valuable and whose acceptance meant entering into a binding agreement. It signified that the recipient obliged himself to perform a defined obligation for the donor, or it acted as a kind of compensation for a favour granted. The exchange of gifts  was governed by the reciprocity principle. Therefore, an object that was a diplomatic gift brought about defined international consequences by virtue of having involved the representatives of the authorities of two states. The acts of presenting a gift and its acceptance were a kind of transaction. These considerations on the practice of presenting objects in diplomacy were inspired by the saddle offered by Turkish Sultan Mustafa II to Stanis³aw Ma³achowski, the Polish envoy for peace talks held in Kar³owice in 1698–99. Currently, the saddle is exhibited in the Wawel Royal Castle museum. The subject of the present paper is an episode in the saddle’s “biography” (as named by Igor Kopytoff) related to its role as a diplomatic gift. Telling the story of the given thing, however, it was impossible to pass over the issue of “its ideal ‘biography’” and of what has become of this thing as time went by and it lost its usability. The saddle as a thing, a gift or a museum exhibit illustrates the different statuses of the same object which are determined by the context of its relations with the human, relations that assign meanings to this object. Given the aim of this paper, the first and the last function of the saddle are treated only superficially, whereas the considerations concentrate on the saddle as a thing displaying the property of agency in the ceremonial process of exchanging gifts in Polish-Turkish diplomatic relations.